Health and rescue services management system during a crisis event - Kyriacou, Efthyvoulos C.; Nicolaidou, Iolie; Hadjichristofi, George; Kyprianou, Stelios; Christou, Synesios; Constantinou, Riana (My University, 2016)
Τhe performance of rescuers and personnel handling major emergencies or crisis events can be significantly improved through continuous training and through technology support. The work done in order to create a system has been discussed which can support both resources and victims during a crisis or major emergency event. More specifically, the system supports real-time management of firefighter teams, rescue teams, health services, and victims during a major disaster. It can be deployed in an ad hoc manner in the disaster area, as a stand-alone infrastructure (using its own telecommunications and power). It mainly consists of a control station, which is installed in the area command centre, the firefighters units, the rescuers units, the ambulance vehicles units, and the telemedicine units that can be used in order to support victim handling at the casualties clearing station. The system has been tested and improved through continuous communication with experts and through professional exercises; the results and conclusions are presented.
Keywords: Telemedicine; Health; Blood pressure